EXPORT POTENTIAL OF UKRAINE AND THE SPECIFIC FEATURES OF ITS IMPLEMENTATION IN TRADE AND ECONOMIC RELATIONS WITH EU COUNTRIES - Атаманчук, Зорина; Романець, Тетяна (SWorldJournal, 2026)
The article analyzes the current state and specific features of the Ukraine’s export potential formation in the context of developing trade and economic relations with the European Union. Based on statistical data, the structure, dynamics, and trends of U